Structural Differentiation and Ambidexterity: The Mediating Role of Integration Mechanisms - Jansen, Justin J. P; Tempelaar, Michiel P; van den Bosch, Frans A. J; Volberda, Henk W (Organization science (Providence, R.I.), 2009)
Prior studies have emphasized that structural attributes are crucial to simultaneously pursuing exploration and exploitation, yet our understanding of antecedents of ambidexterity is still limited. Structural differentiation can help ambidextrous organizations to maintain multiple inconsistent and conflicting demands; however, differentiated exploratory and exploitative activities need to be mobilized, coordinated, integrated, and applied. Based on this idea, we delineate formal and informal senior team integration mechanisms (e.g., contingency rewards and social integration) and formal and informal organizational integration mechanisms (e.g., cross-functional interfaces and connectedness) and examine how they mediate the relationship between structural differentiation and ambidexterity. Overall, our findings suggest that the previously asserted direct effect of structural differentiation on ambidexterity operates through informal senior team (i.e., senior team social integration) and formal organizational (i.e., cross-functional interfaces) integration mechanisms. Through this richer explanation and empirical assessment, we contribute to a greater clarity and better understanding of how organizations may effectively pursue exploration and exploitation simultaneously to achieve ambidexterity.